Analisis Bibilometrik Perkembangan Strategi Komunikasi di Media Sosial Pada Instansi Pemerintahan Dalam Keamanan Siber - Hakiki, Dikhy; Harahap, Hamida Syari; Sulistyanto, Ari (Jurnal Keamanan Nasional, 2024)
The Internet has become one of the means for Government Institutions to provide fast and easy services. It also makes the public more actively monitor the progress of public services. The utilization of Social Media by government agencies is an innovation that maximizes technology. Furthermore, the use of the internet through Social Media requires strategies to cope with the advancements of the times as a means of communication. This research utilizes the Scopus database. The article analyzes the characteristics of publications, researchers, universities, and the contributions of countries in the field of Government Institutions conducting communication strategies through social media from 2013-2024 using bibliometric methods. This method is useful because it involves the quantitative analysis of a large number of literatures, using mathematical and statistical methods. The results show that there are 162 documents or articles with the United States, Spain, United Kingdom, China, Canada, Australia, Malaysia, Brazil, Indonesia, and Italy as the countries published in this field. Policy recommendations include the need to enhance the development of Government Institutions to manage their social media in a planned and measurable manner. Further research is expected to focus on public understanding of information provided by government agencies for long-term comprehensibility.